A LABORATORY SCALE PHOTOELECTRIC EFFECTS APPARATUS TO DETERMINE A WAVELENGTH OF LIGHT FOR HIGH SCHOOL PHYSICS LEARNING MEDIA - Ernawati
The photoelectric effect is a phenomenon where electrons are detached from a metal surface when the metal is exposed to light. In Physics as a subject in high school, the photoelectric effect is included in modern physics material which has abstract concepts that causes students to have difficulty understanding it. One way to address the problem is to adopt experimental methods of photoelectric effects. Of course, in carrying out experimental methods, it would require a set of photoelectrics apparatus. Several study on photoelectrics effect have been conducted, such as by Rimella Diaz (2017) with laser-lighting sources and Risdiyanto (2009) with LED lighting sources. Based on the study, the study that has been carried out is a photoelectric effects tool used to determine the wavelength of the light source used. The study was conducted in several stages which are designing a photoelectric effect tool, manufacturing photoelectric effect tool, tool testing, data analysis and conclusions. Experiments conducted to test the photoelectric effects made by using 1P39 phototube with cesium metal cathode while for the light sources used are blue, green and white LEDs and yellow HPLED of 10 each. The results of the experiments were obtained a wavelength value of the blue LEDs are 436.8 nm – 491 nm, for the green LEDs are 499 nm – 520 nm, for white LEDs are 427 nm – 458 nm and for yellow HPLEDs are 491 nm – 518 nm. The wavelength of the blue and green LEDs correspond with the references while to the yellow HPLED do not fit the references. For the white LEDs should not have the wavelength because of the experiments the value of the blue wavelength was obtained. Based on these experiments, the photoelectric effects apparatus made can be used as high school’s physics learning media to determine the wavelength of an LEDs.